Ecotoxicological effects of salicylic acid in the freshwater fish Salmo trutta fario: antioxidant mechanisms and histological alterations - Nunes, B.
The presence of pharmaceutical drugs in aquatic ecosystems has been widely reported during the past years. Salicylic acid (SA) is mainly used in human medicine as an analgesic and antipyretic drug, being also active in preventing platelet aggregation. To study the ecotoxicological effects potentially elicited by SA in freshwater fish, brown trout individuals (Salmo trutta fario) were chronically exposed (28 days) to this drug, in order to evaluate the enzymatic and histological effects, in both gills and liver. A qualitative and semi-qualitative evaluation of the gills and liver was performed, and also a quantitative evaluation of various lamellar structures. Oxidative stress was quantified trough the determination of glutathione S-transferases (GSTs), glutathione reductase (GRed), total and selenium-dependent glutathione peroxidase (GPx) and Catalase (Cat) activities. Lipid peroxidative damage was also assessed by the quantification of thiobarbituric acid reactive substances (TBARS) in the liver. The here-obtained data showed the occurrence of oxidative stress, reflected by an increased activity of GPx and GRed in the liver; additionally, it was possible to observe nonspecific histological changes in gills. The global significance of the entire set of results is discussed, giving emphasis to the ecological relevance of the responses.